Sexualidades em negociação: a pornografia live streaming no CAM4.com - Rost, Mariana (Universidade do Vale do Rio dos Sinos, 2016)
This Master's theses focuses on the negotiations on CAM4, a live streaming pornography website. This type of pornography consists of sharing live sexual activities over a webcam with the possibility of interaction between those who watch and the person on the video through an online chat beside the video box. The sexual practices are negotiated with tips that participants pay in exchange for specific activities. Through an ethnography about the use of digital media, I analyze the role of sexuality, the notions of eroticism and the circulation of gender attributes on the negotiations made in the transmissions on the website. I am interested in the dynamics of this environment that produces and circulates pornographic material in a context of the pursuit of the authenticity and new technological possibilities. Thus, I identify the mechanisms by which live streaming pornography is organized and how they compete in the production of difference as well as gender and sex technologies. I also aim to examine how money, sex toys and technological artifacts mobilize specific ways to have pleasure. Finally, I seek to understand how this type of pornography can be distributed in political actions in the field of gender relations and sexuality.
Keywords: Pornografia live streaming; Sexualidades; Gênero; Mídias digitais; Autenticidade; Live streaming pornography; Sexualities; Gender; Digital media; Authenticity; ACCNPQ::Ciências Humanas::Sociologia